Unpacking the Complexities of Teacher Identity: Narratives of EFL Teacher in Indonesia (Universitas Negeri Semarang, 2023)
The participant in this study was an English teacher who also held the position of vice principal, and the researchers investigated the complications involved in the construction of a teacher's identity for a teacher of English in Indonesia, representing the expanding number of English instructors. This study used an integrated perspective to investigate the development of English teacher identities, drawing insights from Barcelos' (2015) theory of the relationship between teacher beliefs, teacher identity, and teacher emotions. The approach of narrative inquiry was utilized for the analysis of the data. By conducting an exploration of the life histories of the participant who had learned English and gone on to become an English teacher, this study was able to capture the dynamics of how the fundamental beliefs and feelings of the focused participant interacted with one another and formed the identity of the teacher. This was accomplished by focusing on how the participants had learned English and gone on to become English teachers. To reach this goal, the life stories of individuals who had previously studied English and gone on to become English instructors were investigated.